7x + 2 = -19 (b) 3x - 1/3 = 5 (c) 5x - 4 = 21 (d) -7x = 21 (e) 18 - 7x = -3 (f) 3(x + 4) = 21 (g) 3x - 9 = 5x - 3 (h) 4x + 6 - 7x + 9 = 18 (i) - 4/9 x = - 36 (j) -7/8x - 6 = 8 can any please elp me find the variables in the question

Respuesta :

Answer:

Step-by-step explanation:

a)7x + 2 = -19  {subtract 2 from both sides}

7x + 2 -  2 = -19 - 2

            7x = -21   {Divide both sides by 7}

         7x/7 = -21/7

             x = -3

b) 3x - 1/3 = 5

3x - 1/3 +1/3 = 5 + 1/3  {Add 1/3 to both sides}

               3x =15/3 + 1/3

               3x =16/3

             3x/3 = 16/3*3 {Divide both sides by 3}

                 x =16/9

                 x =1 7/9

c) 5x - 4  = 21

5x -4 + 4 = 21 +4 {Add 4 to both sides}

          5x = 25

       5x/5 = 25/5    {Divide both sides by 5}

            x = 5

d) -7x  = 21 {Divide both sides by -7}

-7x/-7 = 21/-7

        x = -3

e)   18 - 7x = -3

18 - 7x - 18 = -3 - 18   {Subtract 18 from both sides}

          -7x = -21   {Divide both sides by -7}

      -7x/-7 = -21/-7

              x = 3

f)     3(x+4) = 21   {use distributive property}

   3x + 3*4 = 21

    3x  + 12 = 21

3x + 12 - 12 = 21 - 12       {Subtract 12 from both sides}

              3x = 9   {Divide both sides by 3}

           3x/3 = 9/3

                 x = 3

g)     3x - 9 = 5x - 3  {add 9 to both sides}

 3x - 9 + 9 = 5x - 3 + 9

             3x = 5x + 6

       3x - 5x = 5x + 6 - 5x     { subtract 5x form both sides}

             -2x = 6  {Divide both sides by -2}

         -2x/-2 = 6/-2

                 x = -3

h) 4x + 6 - 7x + 9 = 18   {Add the like terms}

           -3x  + 15 = 18  {Subtract 15 from both sides}

      -3x + 15 -15 = 18 - 15

                    -3x = 3   {Divide both sides by -3}

               -3x/-3 = 3/-3

                      x = -1

[tex]i) \frac{-4}{9}x = -36[/tex]

Multiply both sides by 9

[tex]9*\frac{-4}{9}x =9*-36[/tex]

 -4x = -324     {Divide both sides by -4}

-4x/-4 = -324/-4

       x = -81

[tex]j)\frac{-7}{8}x - 6 = 8[/tex]   {Add 6 to both sides}

[tex]\frac{-7}{8}x-6+6=8+6\\\\\frac{-7}{8}x=14\\[/tex]    {Multiply both sides by 8}

[tex]\frac{-7}{8}x*8=14*8\\\\-7x=14*8\\[/tex]       {Divide both sides by -7}

[tex]\frac{-7}{-7}x=\frac{14*8}{-7}[/tex]

x =-2*8

x = -16

ACCESS MORE